Small-sized peripheral squamous cell lung carcinoma with chest wall invasion. (2022) - Otsuka, Shinya; Hiraoka, Kei; Ohtaka, Kazuto; Iwashiro, Nozomu; Kimura, Noriko; Kaga, Kichizo; Ohara, Masanori
Abstract: In lung cancer, chest wall infiltration caused by a tumor with a small diameter is extremely rare. The pathophysiologic features and prognosis of this phenomenon are poorly understood. Here, we report on a case in which a small peripheral lung cancer showed marked invasion into the chest wall. Although complete resection and postoperative adjuvant treatment were performed, lymph node recurrence developed and the patient died in one and a half years. Peripheral lung cancer can show exophytic development and infiltration of the chest wall, leading to poor prognosis, even if the tumor size is relatively small. Highlights: Chest wall invasion by small-sized lung carcinoma Lung tumor adjacent to intrapulmonary air space can show exophytic development Lymph node metastasis with lung cancer with chest wall invasion after complete resection